High thermal conductivity and excellent electrical insulation performance in double-percolated three-phase polymer nanocomposites. (26th May 2017) - Zhang, Dong-Li; Zha, Jun-Wei; Li, Chao-Qun; Li, Wei-Kang; Wang, Si-Jiao; Wen, Yongqiang; Dang, Zhi-Min
Abstract: High voltage direct current (HVDC) cable is attracting more attention during power transmission due to its many advantages. However, the accumulation of space charge, poor breakdown strength and low thermal conductivity of cable insulation layer have been a long-standing obstacle to utilize the HVDC cable applications. Because boron nitride nanosheets (BNNSs) are increasingly demanded in high thermal conductivity insulation materials, herein we report a facile and easy way to prepare styrene-(ethylene-co-butylene)-styrene tri-block copolymer/polypropylene (SEBS/PP) blends filled with BNNSs based on the construction of thermal conductive networks with double-percolation process. The morphology, thermal, and electrical properties of the BNNSs/SEBS/PP nanocomposites were investigated. Scanning electron microscopy showed that the BNNSs were well dispersed in the SEBS phase at low loading of 3 phr. The analysis results on electrical properties illustrated that the direct current (DC) breakdown strength and space charge suppression were remarkably improved by the introduction of BNNSs. In addition, the thermal conductivity of SEBS/PP blends (0.42 W m −1  K −1 ) was increased to 1.38 W m −1  K −1 when doped with 3 phr BNNSs. This nanocomposites with enhanced thermal conductivity and electrical properties have great potential to be used as recyclable insulating materials for HVDC.